2020
DOI: 10.1111/jcmm.15808
|View full text |Cite
|
Sign up to set email alerts
|

Targeting UDP‐glucose dehydrogenase inhibits ovarian cancer growth and metastasis

Abstract: Ovarian cancer is the leading cause of death in patients diagnosed with gynaecologic carcinoma. The American Cancer Society reported approximately 22 530 cases of ovarian cancer and 13 980 cancer-related-deaths in 2019, indicating a relatively high fatality rate. In the case report, over 60% of patients died from ovarian cancer, compared to 15% of those with breast cancer. 1 This high

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 49 publications
(105 reference statements)
0
31
0
Order By: Relevance
“…Recent studies have reported that UGDH affects patient survival [ 34 ], cell proliferation [ 32 , 37 ], cell invasion [ 27 ], cell migration [ 34 , 37 ] and SNAI1 expression [ 28 ]. We set out to confirm these effects of UGDH in our EMT cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have reported that UGDH affects patient survival [ 34 ], cell proliferation [ 32 , 37 ], cell invasion [ 27 ], cell migration [ 34 , 37 ] and SNAI1 expression [ 28 ]. We set out to confirm these effects of UGDH in our EMT cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a growing number of studies have focused on UGDH in cancer, and the roles of UGDH in tumour growth, metastasis and patient survival have been well documented [27,32,[34][35][36][37]. Additionally, UGDH has been connected to EMT [27,28,32,34,75]. Arnold et al [27] reported that UGDH was highly expressed in mesenchymal cells and mesenchymal-like breast cancers and connected UDP-GlcA (the enzymatic product of UGDH) to extracellular matrix remodelling and mesenchymal-like properties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations